Analysis of Uneven Regional Development in North-East, Middle–Southeast, and West-South Regions of Aceh Province - Yayuk Eko Wahyuningsih; Irfan Syah Putra; Eni Meliana (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2017)
Aceh is a province of Indonesia that currently consists of 23 districts/municipalities that are generally divided into three (3) regions, namely, the Northeast (11 districts/municipalities), the Middle-southeast (4 districts) and the Southwest (8 districts/municipalities) regions. These regions have different natural, human, social, political, and cultural resources. These differences have caused uneven economic development, which has further caused developmental disparity among the regions. This study aims to assess the extent of developmental disparity among regions and to analyze the impact of Gross Regional Domestic Product per capita on regional developmental disparity in the three (3) regions of Aceh province in the period of 2000-2014. The data used in this research are secondary data that were obtained from the Central Statistics Agency (BPS), and the Regional Development Planning Board (Badan Perencanaan Daerah/Bappeda) of Aceh Province. To identify the level of inequality, the researcher utilizes Williamson Index;whereas to determine theimpact of Regional GDP per capita on the inequality of regional development, the researcher utilizes a semi logarithmic linear regression model that includes a discussion on the correlationcoefficient (R), determination coefficient (R Square), and t test using SPSS.Based on estimation results, the researcher discovers that, for the North-East region,the value of correlation coefficient (R) is 0.8032, the value of determination coefficient is 64.52%, and the equation for Y isY = -1.8942 + 0,1263X;for the Middle-Southeast region, the value ofcorrelation coefficientis0.6760, the value of determination coefficient is 45.70%, and the equation for Y is Y = 0.6441 + 0,0400X, and;for the Southwest region,the value ofcorrelation coefficientis 0.4045, the value of determination coefficient is 16.36%, and the equation for Y is Y = -0.4703 + 0,0318X. As for the t test, the researcher discovers that for North-East region the per capita regional GDP wastcount> ttable(4.671> 1.7823);for the Middle-Southeast regional tcount<ttable(-3.178<1.7823), and; for the Southwest region tcount<ttable (1.532 <1.7823). These per capita regional GDP values mean that only in the Northeast region does the variable of per capita regional GDP have a real impact on the variables of regional developmental disparity. This is consistent with the fact that the Northeast region is much more advanced and developed than the other two regions.JEL Classification: O10, O11, O15 Keywords: GDP, Index of Williamson and Discrepancy, Per capita GDP, Total of population